Sumbangan Dato Haji Ismail Yusoff (1915-1988) dalam Persuratan Islam di Kelantan - Ab. Hamid, Faisal @ Ahmad Faisal (Jurnal Usuluddin, 2004)
This is a biographical account of a famous Muslim scholar ofKelantan in the post-independent era, Dato Ismail Yusof (1915-1988) the 11th Mufti of Kelantan. This research explains his contribution to the development of Islamic literature in Kelantan, especially when he was the head (chief editor) of Pengasuh for two years. In addition to contributing to Islamic literature, he was also an expert in Islamic education in Kelantan. He had written more than 30 books and 41 articles on various topics. The high quality of his writings are evidence of his expertise. He was considered a far-sighted scholar with a moderate view of khilafiyyat, yet was much firmed with regards to the fundamental teachings of Islam.